Between Courtly Ideal and Christian Purity: How Do the Female Characters in Disney Films Reflect the Medieval Feminine Ideal? - Wolter, Daniel (Mabatim: Journal of Visual Culture, 2024)
This study explores how the feminine ideal and the desired characteristics for women from the Middle Ages, as depicted in etiquette books and Gothic sculpture from that period, are reflected in the female characters of two Disney films set against a medieval backdrop: Snow White and the Seven Dwarfs (1937) and Sleeping Beauty (1959). The goal of this research is to uncover how the medieval feminine ideal merged with the neo-medievalism and conservatism of Walt Disney in the United States during the 1930s and 1950s, leading to the creation of these female characters. Unlike the methods of conveying desired social norms regarding gender roles during the Middle Ages, where one had to visit a church or read manuscripts in order to encounter these messages, twentieth-century American audiences received them via Disney films. These films had a lasting impact on communicating gender role expectations, leaving a significant impression on many generations of viewers since their release. This article examines how these films, set in a medieval context, represent the feminine ideal of that period and discusses the connection between this ideal and Walt Disney’s attitudes, beliefs, and vision regarding gender relations and the ideal of femininity.